Functional and Anti-Nutritional Properties, in-vitro Protein Digestibility and Amino Acid Composition of Dehulled Afzelia africana Seeds: Properties and Composition of Azelia africana Seeds (Biological Sciences - PJSIR, 2010)
Analysis of Afzelia africana seed flour showed that the seeds possessed high water absorption capacity (128.31%), good oil absorption capacity (588.49%) and fairly good emulsion property (35.25%). However, it had the least gelation concentration (6.00% w/v) and foaming properties (8.00%, 3.00%). Anti-nutritional factors were very low, with the highest being phytate (13.59%) and tannin the least (0.43%). Total amino acid composition was 796.6 mg/g protein. Essential amino acids (48.5%) were in high proportion with in-vitro digestibility of 71.5%.